Os significados da religiosidade para docentes supervisores do curso de psicologia - Esteves, Maria Cristina Soares (2009)
This work is based on questionings concerning the pedagogical area in Psychology. It aims at understanding the meanings of religiosity for professors and supervisors acting in Psychology under-graduation courses, since literature tells us that it is practically absent in the formation of a psychologist. Besides, it is hard for professionals to deal with it. In order to analyze this subject from the viewpoint of psychology professors, a qualitative research was developed based on phenomenology, and supported by the method proposed by Forghieri (1993) and Giorgi (1985), in an attempt to look into professors experiences through semi-conductive interviews. The analysis aimed at understanding the meanings they detect in religiosity, and how the latter interferes in their attitudes towards students, both as professors and supervisors. Whenever the religious theme, comes up in the classroom, it provokes different positions, with several directions, depending on how the professor lives and understands his own religiosity. Thus, the meaning of this theme in a person s life history is taken to the classroom, and becomes a part of the formation of future psychologists. This research emphasizes the need to increasingly study the religious experience lived by psychologists and professors, as well as how they influence their theoretical positions and practices, aiming at offering the students a more complete formation